Multimodal 3-D/2-D human islet and duct imaging in exocrine and endocrine lesion environment: associated pancreas tissue remodeling - Chung, Mei-Hsin; Chien, Hung-Jen; Peng, Shih-Jung; Chou, Ya-Hsien; Chiang, Tsai-Chen; Chang, Hsiu-Pi; Lee, Chih-Yuan; Chen, Chien-Chia; Jeng, Yung-Ming; Tien, Yu-Wen; Tang, Shiue-Cheng (American journal of physiology: endocrinology and metabolism, 2022)
We develop a new multimodal 3-D/2-D imaging approach (matched stereomicroscopic, fluorescence, and H&E signals) to examine human duct-islet association in the PDAC surgical margin and cadaveric donor pancreas. In both conditions, peri-PanIN islet aggregation with duct-islet cell clusters was identified. The PanIN-islet cell microadenoma association was unexpectedly detected in the donor pancreas. Our work provides the technical and morphological foundations to simultaneously characterize human islets and ducts to study their association in health and disease. Pancreatic intraepithelial neoplasia (PanIN) and islet cell microadenoma are exocrine and endocrine neoplasms of human pancreas that have been linked to pancreatic ductal adenocarcinoma (PDAC) and neuroendocrine tumor, respectively. However, in health and at the surgical margin of pancreatic cancer, it remains unresolved how to simultaneously characterize duct and islet remodeling to investigate the exocrine-endocrine association in the lesion microenvironment. Here, we develop a new vibratome-based approach to detect, confirm, and analyze the two types of pancreas remodeling via stereo/three-dimensional (3-D) and classic/two-dimensional (2-D) histology. Surgical margins of PDAC ( n = 10, distal) and cadaveric donor pancreases ( n = 10, consecutive cases) were fixed, sectioned by vibratome (350 µm), and surveyed for PanIN and microadenoma via stereomicroscopy. After lesion detection, PanIN and microadenoma were analyzed with 3-D fluorescence imaging and clinical microtome-based histology for confirmation and assessment of microenvironment. Multimodal imaging of PDAC surgical margins and cadaveric donor pancreases detected the peri-PanIN islet aggregation with duct-islet cell clusters. Organ-wide survey of cadaveric donor pancreases shows a marked 2.3-fold increase in the lesion size with the PanIN-islet association vs. without the association. In the survey, we unexpectedly detected the islet cell microadenoma adjacent to (<2 mm) PanIN. Overall, among the 53 early lesions in the cadaveric donor pancreases (PanINs and microadenomas), 81% are featured with the associated exocrine-endocrine tissue remodeling. Multimodal 3-D/2-D tissue imaging reveals local and simultaneous duct and islet remodeling in the cancer surgical margin and cadaveric donor pancreas. In the cadaveric donor pancreas, the peri-PanIN islet aggregation and PanIN-microadenoma association are two major features of pancreas remodeling in the early lesion microenvironment. NEW & NOTEWORTHY We develop a new multimodal 3-D/2-D imaging approach (matched stereomicroscopic, fluorescence, and H&E signals) to examine human duct-islet association in the PDAC surgical margin and cadaveric donor pancreas. In both conditions, peri-PanIN islet aggregation with duct-islet cell clusters was identified. The PanIN-islet cell microadenoma association was unexpectedly detected in the donor pancreas. Our work provides the technical and morphological foundations to simultaneously characterize human islets and ducts to study their association in health and disease.